Sosialisasi Etika Berkomunikasi Digital sebagai Upaya Pencegahan Bullying di Lingkungan SMK Negeri 1 Stabat: Penelitian - Dwika Ardya; Muhammad Irfan Sarif; Afif Asri; Dhimas Prayogi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The rapid development of digital technology among students brings both positive impacts and challenges, one of which is the increasing risk of digital bullying in school environments due to limited understanding of digital communication ethics. This Community Service Program (PKM) aims to improve students’ understanding of digital communication ethics as an effort to prevent bullying at SMKN 1 Stabat. The methods employed include socialization activities, interactive discussions, and the presentation of case studies related to communication behavior in digital spaces. Evaluation was conducted by comparing students’ levels of understanding before and after the program. The results indicate significant improvements across all assessed aspects. Understanding of digital communication ethics increased from 40% to 85%, knowledge of digital bullying rose from 45% to 90%, and students’ awareness of the impacts of bullying improved from 60% to 88%. These percentage increases demonstrate that the socialization of digital communication ethics is effective in enhancing students’ digital literacy and contributes to the creation of a safe and bullying-free school environment. This program is expected to serve as a sustainable preventive education model within educational institutions.